Radio Explorations (transcript Verlag, 2024)
Radio signals keep making material, informational, political, and social connections in this world. Exploring these signals architectonically, the contributors engage with the situatedness of radio signal recordings in nature and with knowledge implied in radio communication. Rooted in experimental design and data feminism, the book presents innovative tools for navigating data by spanning media theory, information studies, and feminist new materialism. This offers an intersectional and post-disciplinary approach to computation, classification, and search that is accessible to artists, technologists, and researchers - facilitating interdisciplinary collaboration and deepening the understanding of information technologies.